Exploring the influence of teachers' academic rank in advancing inclination to TPACK in art education - Masoumeh Shiri; Karim Baigutov (Social Sciences and Humanities Open)
Purpose: This study aims to examine the factors of digital literacy, digital skills, and teachers' academic rank on the level of inclination in TPACK among art teachers at the studied university. Specifically, the study investigates how teachers' academic rank can influence their inclination toward TPACK. Additionally, it classifies and analyzes teachers' digital literacy and digital skills based on their academic rank. Design/methodology: This study employs both survey and descriptive research methodologies to create a survey-based approach for measuring teachers' digital literacy, digital skills, and their inclination towards TPACK, using a sample of 35 art teachers at the studied university. Furthermore, observational methods were used to describe the current situation and gather data. Findings: The findings reveal that teachers' academic rank plays a significant role in the increase or decrease of their level of digital literacy. Overall, teachers' digital skills were found to be lower than their digital literacy, indicating the challenges teachers face in solving hardware and software problems when using TPACK. Additionally, the study found that inclination of teachers to adopt teaching methods that integrate technology, art, and educational content was rated highly. Conclusion: The results indicate that teachers' academic rank significantly influences their level of digital literacy, which consequently increases their inclination towards TPACK. The study also found that lecturers have lower digital skills and, therefore, less inclination towards TPACK.